PENATALAKSANAAN SUMBATAN JALAN NAFAS ATAS (JACKSON IV) DENGAN KRIKOTIROTOMI DAN TRAKEOSTOMI - Tobing, Jerry (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
Cricotirotomy is an action to overcome the airway obstruction in the larynx. This is done by opening the cricothyroid membrane quickly by using a needle (chrycothyrotomy needle). Cricotirotomy is usually done in an emergency with a shorter time. To take action, it is necessary to do the anatomy of the larynx and trachea in order to understand the surgical technique.